2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications 2011
DOI: 10.1109/pimrc.2011.6140021
|View full text |Cite
|
Sign up to set email alerts
|

GSM downlink spectrum occupancy modeling

Abstract: In this article the spectrum occupancy of a GSM900 and a DCS1800 band as an analog power or binary quantized power is modeled. In the case of analog power it is presented histograms of the power distribution during one working day. In the case of quantized power it presents the two time statistics, the time period of opportunities distribution and the time between opportunities distribution. The measurement setup is standing in line of sight with the base station. Also, the measurement setup in terms of maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…The slight deviation from the logs may be due to nonpanOULU WLAN traffic, non-traffic beacon signals and other interferences. Similar occupancy results for GSM carriers over one working day were obtained at the University of Aveiro campus in Portugal [8]. Figure 4 shows the variation of the spectrum occupancy of a single 200 kHz GSM1800 channel consisting of 8 time-division multiple access (TDMA) slots.…”
Section: Figure 2 Impact Of the Decision Threshold On The Spectrum Ocsupporting
confidence: 59%
“…The slight deviation from the logs may be due to nonpanOULU WLAN traffic, non-traffic beacon signals and other interferences. Similar occupancy results for GSM carriers over one working day were obtained at the University of Aveiro campus in Portugal [8]. Figure 4 shows the variation of the spectrum occupancy of a single 200 kHz GSM1800 channel consisting of 8 time-division multiple access (TDMA) slots.…”
Section: Figure 2 Impact Of the Decision Threshold On The Spectrum Ocsupporting
confidence: 59%
“…In [35], the PDF of the power level over several selected channels of GSM system was obtained by calculating the probability over all measure-ments obtained in one day in that channel. The PDF is in general asymmetric.…”
Section: A Cdf and Pdfmentioning
confidence: 99%
“…On the other hand, it was also pointed out that such conclusions heavily rely on the frequencies and times chosen. In [35], the time interval between two opportunities was studied for the GSM system. This is actually the burst length considered in [39].…”
Section: A Cdf and Pdfmentioning
confidence: 99%
“…The authors used a spectrum analyzer in the GSM band to determine the average power spectral density. Similarly, [8] also identifies and characterizes the channel opportunities over a GSM network in Aveiro, Portugal. The results have showed that RF-spectrum opportunities over GSM licensed frequencies follow an exponential behavior.…”
Section: A Related Workmentioning
confidence: 99%